Compassionate use of remdesivir in pregnancy: a case series - Shah, Jui R.; Parikh, Khushali P.; Suthar, Aayushi A.; Shah, Sushma R.; Malhotra, Supriya D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Coronavirus disease 2019 (COVID-19) has resulted in an unprecedented global healthcare crisis. One special population that poses a challenge is pregnant women with COVID-19. However, there is limited data on treatment options for severe coronavirus disease in pregnancy. Remdesivir, an antiviral drug, is currently being studied as a potential treatment of COVID-19 pneumonia. Nevertheless, pregnant women are also being excluded from various clinical trials for the disease. There are some studies mentioned in the literature which have shown no adverse effects of remdesivir during pregnancy. In this study, we present four serial cases of COVID-19 in pregnant women with moderate to severe symptoms who were treated with remdesivir. All of the them showed positive fetal outcome without any birth defects or malformations. However, further studies are necessary to evaluate the biosafety and effects of remdesivir in pregnant women.